An electromagnetism-like metaheuristic for open-shop problems with no buffer - Bahman Naderi; Esmaeil Najafi; Mehdi Yazdani (Journal of Industrial Engineering International, 2012)
This paper considers open-shop scheduling with no intermediate buffer to minimize total tardiness. This problem occurs in many production settings, in the plastic molding, chemical, and food processing industries. The paper mathematically formulates the problem by a mixed integer linear program. The problem can be optimally solved by the model. The paper also develops a novel metaheuristic based on an electromagnetism algorithm to solve the large-sized problems. The paper conducts two computational experiments. The first includes small-sized instances by which the mathematical model and general performance of the proposed metaheuristic are evaluated. The second evaluates the metaheuristic for its performance to solve some large-sized instances. The results show that the model and algorithm are effective to deal with the problem.
Keywords: 650; scheduling; open shop with no buffer; mixed integer linear programming; electromagnetism algorithm